CEOs on a mission : reimagining CEO activism, development, and difference - Adae, Eric Kwame (Emerald Publishing Limited, 2023)
Today, CEOs function increasingly as social activists, often pursuing socio-political causes which fall outside of their usual pursuit of the corporate or financial bottom line. Based on a series of long interviews and the application of alternative theoretical lenses, this book examines this phenomenon within the African context on the road to creating a CEO Activism Development Model. Addressing the gender disparity that continues to persist in this field, chapters consider alternative perspectives on corporate socio-political involvement, including motivations, tactics, safeguards and guidelines. Through a distinct postmodern lens, Eric Kwame Adae further explores how CEO activism fits into more specific African contexts and intersects with certain Afrocentric philosophies, including Caritas, Ubuntu philosophy and Africapitalism. Breaking new ground in his analysis of CEO activism within a non-Western sociocultural context, Eric Kwame Adae presents an exciting exploration of the theoretical, managerial, practical and methodological implications of CEO activism today.
Keywords: Chief executive officers -- Africa -- Attitudes.; Chief executive officers -- Africa -- Interviews.; Social responsibility of business -- Africa.; Business & Economics -- Management.; Management: leadership & motivation.; elektronické knihy; electronic books